Hermann Stehr – a compliant or an involuntar representative of National Socialism? - Gołaszewski, Marcin (Acta Universitatis Lodziensis. Folia Germanica, 2017)
Herman Stehr (1864–1940) belonged to the generation of writers who had the chance to establish a serious opposition against National Socialism during the Weimar Republic, the Fascist movement and the Third Reich. Not only their age but also their experience predestined them to assume such an honourable position. Hermann Stehr, at the early stage of his career, was considered a modern writer, not only because of his writings but also because of his political views, when in the 1920s he took an active part in the building of democratic structures of the Weimer Republic. Around 1930/31 a change occurred his work and in his political views.From this time onwards he actively supported the Nazis and legitimized their politics in his writings both nationally and internationally. The symbiosis between him and the Nazis became more and more visible as they started promoting him as one of the leading German writers.The aim of this paper is to present one of the most renowned German authors of the first half of the 20th century, who due to his conformism during the Third Reich lost his chance to defend humanistic values.Consequently, this paper proves that it is a grave error to classify Stehr, a writers of conservative views, as part of Inner Emigration.Hermann Stehr most certainly did not belong to that group.